Selective laser melting of titanium-tantalum : microstructure and mechanical properties - Chen, Joan Clara Si Yu (2015)
The primary objective of this project is to characterize the mechanical and microstructural properties of titanium-tantalum (Ti-Ta) alloy in a 1:1 weight ratio produced by the selective laser melting (SLM) process. SLM is an additive manufacturing (AM) technique which produces parts layer-by-layer through the use of a 3-dimensional (3D) computer-aided design (CAD) model. Fully dense functional parts of complex geometries and enhanced microstructures can be fabricated directly from SLM, making it suitable for a range of applications. Its ability to process metals with high melting points makes it a suitable process for the Ti-Ta alloy as tantalum has a very high melting point, which makes it unsuitable for conventional production methods. In the orthopedic industry, biomedical implants with a lower Young’s modulus were found to be more suitable for osseointegration. Upon addition of tantalum to titanium, tensile test results showed the Young’s modulus of SLM-produced Ti-Ta alloy was reduced to a value of 74.75 ± 5.30 GPa as compared to SLM-produced commercially pure titanium (cpTi) (107.46 ± 1.21 GPa) and Ti-6Al-4V (119.06 ± 13.40 GPa). The alloy also displayed a high value of strength, with ultimate tensile strength values of 924.64 ± 9.06 MPa, comparable to that of Ti-6Al-4V (1180.70 ± 102.74 MPa) and higher than cpTi (703.06 ± 16.22 MPa). Ti-Ta alloy also displayed a high hardness value of 284.50 ± 11.55 HV and 282.70 ± 10.29 HV in its x-y and y-z planes respectively. The optimal processing parameters for the Ti-50 wt% Ta alloy were also discovered through the course of this report.